Analysis of manganese crusts from Galapagos - Willard S Moore; Peter R Vogt (PANGAEA, 1976)
Manganese oxide crusts similar to those reported from the Mid-Atlantic Ridge rift valley by Scott et al., 1974 (https://doi.pangaea.de/10.1594/PANGAEA.848726) were dredged at two sites near the Galapagos spreading axis on ocean floor estimated from magnetic anomalies to be 2.4 and 0.3 m.y. old. Compared to the typical ocean-floor manganese deposits attributed to precipitation from seawater, the 2-6 cm thick manganese crusts reported here exhibit very low Fe/Mn and low 232Th/238U ratios, as well as lower transition metal and higher manganese concentrations. The manganese crusts were deposited several orders of magnitude faster than the more common hydrogenous nodules; this fact together with other geochemical characteristics and the geophysical environment suggests the manganese deposits reported here are of hydrothermal origin.
Supplement to: Moore, WS; Vogt, PR (1976): Hydrothermal manganese crusts from two sites near the Galapagos spreading axis. Earth and Planetary Science Letters, 29(2), 349-356, https://doi.org/10.1016/0012-821X(76)90139-4